Models and Practice of Retail Location on the Romanian Market - Gerard Cazabat; Mihaela Gabriela Belu; Ioan Popa; Dorel Mihai Paraschiv (Amfiteatru Economic Journal, 2017)
This paper makes a review of the main types of location, respectively of probability models, gravity models, utility models, location- allocation, but also of new spatial analysis instruments. In this context, we emphasize the fact that the new location models, based on a geographic information system and the Big Data analysis instruments, open new opportunities for the practical location decision based on a larger set of criteria and by taking the market dynamics into account. The paper has the following objectives: to study the theoretical basis of location models, i.e. of the criteria (the variables) used and to compare them with the criteria used currently in decision-making practice. The study is based on qualitative research investigating the opinions of decision -makers in the area of distribution regarding the location strategy of new stores. The research findings confirm the existence of differences between the criteria retained by location models and the practice of distribution companies on the Romanian market. This type of approach – models and practices of location for distribution companies – is a novelty for the Romanian market. The study can be useful both for research (perfecting the location models vis-a-vis present-day evolutions of the business environment), as well as for the decision makers in distribution (the valorization of research findings in decisionmaking practice).
Keywords: L81; O33; L86; 330; location models; distribution companies; optimal location; Geographic Information System (GIS); Big Data